2012
DOI: 10.1016/j.immuni.2011.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Stat3 and Gfi-1 Transcription Factors Control Th17 Cell Immunosuppressive Activity via the Regulation of Ectonucleotidase Expression

Abstract: Although Th17 cells are known to promote tissue inflammation and autoimmunity, their role during cancer progression remains elusive. Here, we showed that in vitro Th17 cells generated with the cytokines IL-6 and TGF-β expressed CD39 and CD73 ectonucleotidases, leading to adenosine release and the subsequent suppression of CD4(+) and CD8(+) T cell effector functions. The IL-6-mediated activation of the transcription factor Stat3 and the TGF-β-driven downregulation of Gfi-1 transcription factor were both essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
264
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(286 citation statements)
references
References 44 publications
14
264
2
6
Order By: Relevance
“…10 In order to explore the role of this pathway in the induction of CD73 expression on human monocytes, we tested if sPE-treatment triggers STAT3 phosphorylation. Exposure of CD14 C cells to sPE indeed resulted in significant STAT3 phosphorylation at 30 min, with sustained kinetics, as it was still significantly elevated at 2 h and 4 h compared with that in untreated cells (Fig.…”
Section: Cd73 Induction On Cd14 C Cells By Spe Is Enhanced By Stat3 Imentioning
confidence: 99%
See 2 more Smart Citations
“…10 In order to explore the role of this pathway in the induction of CD73 expression on human monocytes, we tested if sPE-treatment triggers STAT3 phosphorylation. Exposure of CD14 C cells to sPE indeed resulted in significant STAT3 phosphorylation at 30 min, with sustained kinetics, as it was still significantly elevated at 2 h and 4 h compared with that in untreated cells (Fig.…”
Section: Cd73 Induction On Cd14 C Cells By Spe Is Enhanced By Stat3 Imentioning
confidence: 99%
“…1 Double positive cells or extracellular vesicles, such as exosomes, 8 can act as efficient enzymedelivery systems reaching distant sites. The co-expression of these enzymes on immune cells has been demonstrated for activated mouse Treg and Th17 cells, 9,10 but untreated human Tregs in the circulation only express low levels of intracellular CD73. 11 Mouse peritoneal macrophages may also co-express these enzymes, 12 whereas healthy non-activated human blood monocytes and macrophages have abundant expression of CD39 but not CD73 on the cell surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cette IL-6 agit de manière autocrine sur les MDSC et induit la phosphorylation de Stat3, qui relaye l'activité immunosuppressive des MDSC [32]. L'IL-6 agit aussi sur les lymphocytes Th17, en influençant l'expression à leur surface des ectonucléotidases CD39 et CD73, qui jouent un rôle essentiel dans l'immunosuppression via leur production d'adénosine [18]. Chez l'homme, il a été montré qu'elle pouvait bloquer la maturation des cellules dendritiques [33].…”
Section: La Prostaglandine E2 (Pge2)unclassified
“…4 Beyond its contribution to the suppressive activity of Tregs, it has been shown that Th17 cells isolated from various experimental tumor models express not only CD39, but also CD73, and that the expression of these ectonucleotidases determines the immunoregulatory function of Th17 cells. 5 Furthermore, an examination of ovarian cancer specimens revealed that tumor cells express CD39 and that CD39 C ovarian cancer cells generate adenosine, which suppresses T-and NK-cell antitumor responses. 6 Using a large cohort of 500 human tumor and normal histologic samples from 18 of the most common types of cancer, we reported that CD39 is absent or weakly expressed in normal samples, except in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%